1997
DOI: 10.1021/jp961708w
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Studies of Fullerene C60/Benzene Solvates

Abstract: Stable van der Waals-bonded C 60 /benzene solvates were prepared using a novel crystallization technique. Solid-state NMR measurements on highly crystalline solvate under liquid benzene show that there is very little interaction between benzene and the C 60 molecules and that the rotation of C 60 at room temperature is not hindered. The magnetization transfer between benzene protons and local C 60 molecules is highly inefficient. Three benzene species have been found in the solvate: two, nearly freely mobile, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…Pure crystalline fullerene is known to show a molecular rotor, 14 having a diameter of 7 angstroms at room temperature, and fullerene readily forms solid solvates with several host solvents such as n-pentane, 15 hexane, 14,16 ndecane, 17 and benzene. 14 These intrinsic characteristics of fullerene prompted us to prepare homogeneous fullerene-dispersed polymeric membranes (i.e., fullerene/polymer blend membranes), and to investigate gas permeation through the fullerene membranes where the fullerene is spinning as a molecular rotor and solvates with penetrant gases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure crystalline fullerene is known to show a molecular rotor, 14 having a diameter of 7 angstroms at room temperature, and fullerene readily forms solid solvates with several host solvents such as n-pentane, 15 hexane, 14,16 ndecane, 17 and benzene. 14 These intrinsic characteristics of fullerene prompted us to prepare homogeneous fullerene-dispersed polymeric membranes (i.e., fullerene/polymer blend membranes), and to investigate gas permeation through the fullerene membranes where the fullerene is spinning as a molecular rotor and solvates with penetrant gases.…”
Section: Introductionmentioning
confidence: 99%
“…14 These intrinsic characteristics of fullerene prompted us to prepare homogeneous fullerene-dispersed polymeric membranes (i.e., fullerene/polymer blend membranes), and to investigate gas permeation through the fullerene membranes where the fullerene is spinning as a molecular rotor and solvates with penetrant gases.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization from solutions usually produces C 60 solvated structures [9][10][11][12]. It has been found that C 60 nanorods fabricated from solutions of C 60 in m-xylene have a single-crystalline C 60 *1m-xylene solvated structure [7].…”
Section: Introductionmentioning
confidence: 99%
“…8 -12 Pure crystalline fullerene is known to show a molecular rotor 13 having a diameter of 7 angstroms at room temperature, and fullerene readily forms solid solvates with several host solvents such as n-pentane, 14 hexane, 13,15 ndecane, 16 and benzene. 13 These intrinsic characteristics of fullerene prompted us to prepare homogeneous fullerene-dispersed polymeric membranes (i.e., fullerene/polymer blend membranes) and to investigate gas permeation through the fullerene membranes where the fullerene is spinning as a molecular rotor and forms solvates with penetrant gases.…”
Section: Introductionmentioning
confidence: 99%